2004
DOI: 10.6090/jarq.38.227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Side Vents and Span Numbers on Wind-Induced Natural Ventilation of a Gothic Multi-Span Greenhouse

Abstract: In this paper, the effects of wind speed, side ventilators and span numbers on gothic type multi-span greenhouse natural ventilation were studied by numerical simulation using the Computational Fluid Dynamics (CFD) approach. The realizable k-ε model was used for the turbulence model in the simulations. The results showed that the maximum greenhouse ventilation rate was achieved when both side and roof vents were used for ventilation. Without the existence of buoyancy effect in the computations, it was found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 8 publications
1
21
0
1
Order By: Relevance
“…CFD has also been used for the design of more efficient ventilation systems. For instance Kacira et al (2004) and Baeza et al (2009) conducted CFD simulations to investigate the effect of side vents in relation to the number of spans. Both studies showed the importance of side ventilation combined with roof ventilation in large greenhouses.…”
Section: Introductionmentioning
confidence: 99%
“…CFD has also been used for the design of more efficient ventilation systems. For instance Kacira et al (2004) and Baeza et al (2009) conducted CFD simulations to investigate the effect of side vents in relation to the number of spans. Both studies showed the importance of side ventilation combined with roof ventilation in large greenhouses.…”
Section: Introductionmentioning
confidence: 99%
“…Their results provide valuable guidance for ventilation system management; however, they are limited to specific greenhouse structures and local climate conditions. So far, most numerical studies of natural ventilation have focused on greenhouse climate and ventilation performance during the summer (Baeza et al, 2009;Bartzanas et al, 2004;Fatnassi et al, 2003Fatnassi et al, , 2006Hong et al, 2008;Kacira et al, 1998Kacira et al, , 2004Kichah, Bournet, Migeon, & Boulard, 2012;Nebbali et al, 2012;Ould Khaoua et al, 2006;Teitel et al, 2008). Few have examined the effect of vent opening on greenhouse climates during the different seasons of summer and winter when natural ventilation is respectively used for cooling and dehumidification.…”
Section: Introductionmentioning
confidence: 99%
“…In the greenhouse engineering community, many researchers have employed CFD to study the effects of greenhouse design (Bartzanas, Boulard, & Kittas, 2004;, Bournet, Ould Khaoua, Boulard, Migeon, & Chassériaux, 2007Hong et al, 2008;Kacira, Sase, & Okushima, 2004;Kacira, Short, & Stowell, 1998;Kittas and Bartzanas, 2007;Lee, Short, Sase, Okushima, & Qiu, 2000;Ould Khaoua, Bournet, Migeon, Boulard, & Chassériaux, 2006), specific equipment (Baeza et al, 2009;Fatnassi, Boulard, & Bouirden, 2003;Fatnassi, Boulard, Poncet, & Chave, 2006;Montero et al, 2013;Tamimi, Kacira, Choi, & An, 2013) and external weather conditions (Hong et al, 2008;Nebbali, Roy, & Boulard, 2012; Ould 400 K. He et al Khaoua et al, 2006;Teitel, Ziskind, Liran, Dubovsky, & Letan, 2008;Tong et al, 2009) on greenhouse climates. Their results provide valuable guidance for ventilation system management; however, they are limited to specific greenhouse structures and local climate conditions.…”
Section: Introductionmentioning
confidence: 99%
“…CFD has been used to study the effects of side vent opening size and location on airflow patterns and temperature distribution in naturally ventilated greenhouses (Lee and Short, 2000). Kacira et al (2004) analyzed the effect of wind speed, side ventilators, and span numbers on ventilation rates using the CFD approach, showing that when both side and roof ventilators were used, maximum greenhouse ventilation rates were achieved. Lee et al (2002) used CFD models to study the effect of roof vent opening of fully open-roof style multi-span greenhouses, and validated the output with particle image velocimetry (PIV) data.…”
Section: Simulationmentioning
confidence: 99%